EUFEMISME DALAM PERTUTURAN BAHASA MINANGKABAU OLEH MASYARAKAT SUNGAYANG (Euphemism in Minangkabau Language Speech by Sungayang Resident) - Himyati, Eva (Salingka, 2016)
This study is aimed to discuss euphemism in Minangkabau speech spoken by Sungayang people that recently has begun to reduce, especially among young generation. The methodused is descriptive qualitative with deep interview (triangulation) to some informen (recording) dan fieldnote technique. Then, the data were analyzed by matching, distributing reference, interpreting, and ortography-method. The result shows there are three forms of euphemism: mistic, taboo, dan social. The mistic euphemisme is inyiak, dubili, and pauni. Then, taboo euphemism is kaduik, susu, indak sumbahyang, baintaian, and buntiang. Social euphemisme is makanlah (tuak), gadih, dukuang, licin, buruak, duto, iku, lah dak ulu, and ndak banuni. In conclusion, there are three forms of euphemisme found, they are mistic, taboo, and social euphemisme in Minangkabau speech by Sungayang people.